A Two-dimensional Transmission Counter with a Backgammon-Drift Read-Out Technique - Sutomo Budihardjo; Hajime Fujimura; Akihiro Nohtomi; Yusuke Uozumi; Masaru Matoba (PRIMA - Aplikasi dan Rekayasa dalam Bidang Iptek Nuklir, 2006)
AbstractA  new  type  of  two-dimensional  position  sensitive  gas  counter  for  transmission  counter  with  a backgammon-shaped   flat electrode  has been developed.  The two dimensional  position  read-out can  be  achieved  with  the  combination  of  the  backgammon-shaped   flat  electrode  read-out.  as horizontal position  and the drift time measurement  read-out  as vertical position.  The gas counter is designed  as a transmission  trajectory counter that can be used to determined  angle of incident charged particle  in the charged particle  detecting system.  To check the characteristics of this gas counter, test experiments are performed with a coincidence  plastic scintillation  counter  and   p - ray source of  90Sr.